Isolating, characterizing, and utilizing Trichoderma asperellum to antagonize Neurospora spp. causing scab disease on King mandarin fruits (Citrus sinensis) - Khuong, Nguyen Quoc; Ngoc, Le Yen; Thuan, Vo Minh; Hiep, Phan Chan; Trong, Nguyen Duc; Quang, Le Thanh; Thu, Le Thi My; Huy, Nguyen Gia; Nhan, Tran Chi; Xuan, Ly Ngoc Thanh; Xuan, Do Thi (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
The research aimed to (i) isolate, select, and assess the pathogenic potential of fungi that pose a risk of causing scab disease on King mandarin fruits (Citrus sinensis), and (ii) evaluate the antagonistic potential of Trichoderma spp. against Neurospora spp., , which cause scab disease on King mandarin fruits under in vitro conditions. The isolation process identified four fungal strains from ten King mandarin fruits showing scab symptoms, collected from ten orchards in Vung Liem District, Vinh Long Province. The three most virulent scab-causing fungal strains were KMS-01, KMS-02, and KMS-04, with growth diameters of 7.60–7.63 cm after 72 hours of culture (HoC). Additionally, the antagonistic ability of 50 Trichoderma spp. strains against Neurospora spp. ranged from 49.8% to 87.6% at 72 HoC. Among these, three Trichoderma spp. strains—T-SP03, T-SP26, and T-SP41—exhibited high antagonistic efficiency (86.1%–87.7%) against all three scab-causing strains. Based on the ITS region, the pathogenic fungal strains were identified as Neurospora intermedia KMS-01, N. intermedia KMS-02, and N. crassa KMS-04, while the Trichoderma spp. strains were identified as Trichoderma asperellum T-SP03, T-SP26, and T-SP41 with 100% similarity. T. asperellum shows potential as a biological control agent against Neurospora spp., the causative agents of scab disease in King mandarin.